The Role of Metformin in Metabolic Disturbances during Pregnancy: Polycystic Ovary Syndrome and Gestational Diabetes Mellitus - Rojas, Joselyn; Chávez-Castillo, Mervin; Bermúdez, Valmore (International Journal of Reproductive Medicine, 2014)
Maintenance of gestation implicates complex function of multiple endocrine mechanisms, and disruptions of the global metabolic environment prompt profound consequences on fetomaternal well-being during pregnancy and postpartum. Polycystic Ovary Syndrome (PCOS) and gestational diabetes mellitus (GDM) are very frequent conditions which increase risk for pregnancy complications, including early pregnancy loss, pregnancy-induced hypertensive disorders, and preterm labor, among many others. Insulin resistance (IR) plays a pivotal role in the pathogenesis of both PCOS and GDM, representing an important therapeutic target, with metformin being the most widely prescribed insulin-sensitizing antidiabetic drug. Although traditional views neglect use of oral antidiabetic agents during pregnancy, increasing evidence of safety during gestation has led to metformin now being recognized as a valuable tool in prevention of IR-related pregnancy complications and management of GDM. Metformin has been demonstrated to reduce rates of early pregnancy loss and onset of GDM in women with PCOS, and it appears to offer better metabolic control than insulin and other oral antidiabetic drugs during pregnancy. This review aims to summarize key aspects of current evidence concerning molecular and epidemiological knowledge on metformin use during pregnancy in the setting of PCOS and GDM.